THE RESEARCH OF SELF-REGULATE SKILLS DEVELOPMENT THROUGH THE INFORMATION TECHNOLOGIES BY MEANS OF GEOGRAPHICAL CURRICULUM - FOLTÝNOVÁ, Darina (Journal of Technology and Information Education, 2009)
The paper is focused on the questions of self-regulation and possibilities of its development through the information technologies. The author's main aim was to suggest the way how to diagnose level of self - regulate skills development by pupils of basic school and to check by the experimental method whether teaching using information technologies supports self - regulate skills development.The sense of the research was to offer the new idea for how to transfer questions of self - regulation through information technologies into the concrete situations in geography teaching so that pupils have the opportunity to look in their thinking and cognitive procedures. The results prove that it is possible to draw the geography teaching so that pupils use information technologies along with the geographical knowledge with the aim of to achieve required self - regulate skills development.
Keywords: self-regulation; self-regulate skills; experimental method; information technologies; geography teaching